Favorable economic development environment industrial and innovative infrastructure (Journal of Economic Research & Business Administration, 2018)
The article explores the formation of a favorable economic environment for the development ofindustrial and innovation infrastructure. As its main components are determined: legislative and legalsupport for economic initiatives, creation of equal conditions for participants in the innovation process, deepening public-private partnership in the implementation of innovative projects, introducing tools tostimulate the interrelation between science and production, encouraging the identification of non-statesources of funding, granting tax breaks and vacations, support and development of venture business.The authors of the article argue that the creation of a favorable economic environment contributes to thecreation of new innovation-diversified, as well as the development of existing elements of the industrialinnovativeinfrastructure, including technology parks, technological business incubators, and non-stateinnovation funds.